Probable mechanisms involved in the muscle gaping of rainbow trout (Oncorhynchus mykiss) - Mapstone, Samantha Jane (Stellenbosch : Stellenbosch University, 2012)
Dissertation (M.Sc. in Food Science) -- University of Stellenbosch, 1998.